2022
DOI: 10.3390/ijms23126872
|View full text |Cite
|
Sign up to set email alerts
|

IgG from Adult Atopic Dermatitis (AD) Patients Induces Nonatopic Neonatal Thymic Gamma–Delta T Cells (γδT) to Acquire IL-22/IL-17 Secretion Profile with Skin-Homing Properties and Epigenetic Implications Mediated by miRNA

Abstract: γδT cells mature in the human thymus, and mainly produce IL-17A or IFN-γ, but can also produce IL-22 and modulate a variety of immune responses. Here, we aimed to evaluate whether IgG from AD patients (AD IgG) can functionally modulate thymic nonatopic γδT cells. Thymic tissues were obtained from 12 infants who had not had an atopic history. Thymocytes were cultured in mock condition, or in the presence of either AD IgG or therapeutic intravenous IgG (IVIg). Following these treatments, intracellular cytokine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…This study assessed the effect of IgG from AD patients on non-atopic neonatal thymic γδT cells and demonstrated that IgG from AD patients could downregulate the expression of α4β7 and up-regulate the expression of CLA homing molecules on γδT cells. This study suggested that IgG from AD patients may exert some role in modulating homing properties of T cells during its maturation on the thymus, inducing a skin-homing profile (CLA+), which may corroborate with the elucidation of AD development [ 32 ]. Additionally, the same study demonstrated that IgG from AD patients induced the production of IFN-γ, IL-17, and IL-22 and reduced the apoptosis on thymic γδT cells, corroborating not only with a skin-homing profile but also a cytokine secretion profile and an anti-apoptotic profile that may play some role on AD development.…”
Section: Experimental Evidence On the Immune Tolerance Induced By Iggsupporting
confidence: 53%
“…This study assessed the effect of IgG from AD patients on non-atopic neonatal thymic γδT cells and demonstrated that IgG from AD patients could downregulate the expression of α4β7 and up-regulate the expression of CLA homing molecules on γδT cells. This study suggested that IgG from AD patients may exert some role in modulating homing properties of T cells during its maturation on the thymus, inducing a skin-homing profile (CLA+), which may corroborate with the elucidation of AD development [ 32 ]. Additionally, the same study demonstrated that IgG from AD patients induced the production of IFN-γ, IL-17, and IL-22 and reduced the apoptosis on thymic γδT cells, corroborating not only with a skin-homing profile but also a cytokine secretion profile and an anti-apoptotic profile that may play some role on AD development.…”
Section: Experimental Evidence On the Immune Tolerance Induced By Iggsupporting
confidence: 53%
“…Previously, our research group demonstrated that the human thymus can generate IL-10-producing regulatory B cells (B10) in response to stimulation with polyclonal IgG from individuals with allergies 18 . In recent years, the immunomodulatory effects of polyclonal IgG have been observed both in vitro 30 34 and in vivo 35 38 , primarily focusing on T cell populations in murine and human systems.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that differences in hormones and genes are considered to have an impact on both disease and health status [ 3 ]. Recently, expressions of miRNAs have been particularly highlighted due to their various effects on downstream signal pathways [ 5 ], including immuno-related cytokines [ 6 ]. To explain the reason for generally worse long-term outcomes in female KTx patients, we investigated the pathology of kidney graft injuries and collected data regarding immune-related serum miRNA to study the possible correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that differences in hormones and genes are considered to have an impact on diseases and health status [ 3 , 4 ]. Recently, expressions of microRNA (miRNA) have been particularly highlighted due to its various effects on downstream signal pathways [ 5 ], including proinflammatory cytokines and anti-inflammatory cytokines [ 6 ]. MiRNAs are groups of non-coding RNAs possessing essential cellular functions such as cell proliferation, cell differentiation, organ development and immuno-regulation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%